Extraordinary movements of the Denali caribou herd following the perfect storm - Adams, Layne G.; Dale, Bruce W.; Roffler, Gretchen H. (Rangifer, 2005)
Although historic literature is replete with anecdotes about atypical and far-reaching movements of caribou (Rangifer tarandus granti) herds in Alaska, very few such events have been described since the late 1970s proliferation of radiotelemetry studies in the region. In September 1992, several herds in Alaska made unusual movements away from their typical year-round ranges as a result of highly unusual weather conditions that affected a broad swath of the state. We describe the movements of 113 radiocollared caribou from the Denali caribou herd during this phenomenon and the subsequent year. The majority of caribou in the Denali Herd left their typical range during 26—28 September 1992, traveling distances up to 221 km and remained out of the area through much of the winter. While the outmigration was highly consolidated and easily noticed, the return was protracted with caribou drifting back to their typical range from October 1992 to early September 1993. All radiocollared caribou that survived the 1992—93 winter ultimately returned to their typical year-round range.